2010
DOI: 10.1093/sleep/33.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the PER3 Promoter Associates with Diurnal Preference and Delayed Sleep Phase Disorder

Abstract: Polymorphisms in the PER3 promoter could affect its expression, leading to potential differences in the observed functions of PER3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 45 publications
3
81
1
2
Order By: Relevance
“…The authors propose that SP1 acts with BMAL1 to coregulate circadian gene expression. We have previously shown that the promoter region of human PER3 contains two SP1 sites adjacent to two tandem noncanonical E-box motifs and that a variable number tandemrepeat polymorphism in the PER3 promoter removes one of these SP1 sites and is associated with differences in the levels of reporter gene expression (37). Thus, these data are consistent with a role for SP1 in the regulation of circadian gene expression.…”
Section: Transcripts and Associated Molecular Processes Affected By Dsupporting
confidence: 71%
“…The authors propose that SP1 acts with BMAL1 to coregulate circadian gene expression. We have previously shown that the promoter region of human PER3 contains two SP1 sites adjacent to two tandem noncanonical E-box motifs and that a variable number tandemrepeat polymorphism in the PER3 promoter removes one of these SP1 sites and is associated with differences in the levels of reporter gene expression (37). Thus, these data are consistent with a role for SP1 in the regulation of circadian gene expression.…”
Section: Transcripts and Associated Molecular Processes Affected By Dsupporting
confidence: 71%
“…In addition, melatonin – which is often suppressed in night workers – exhibits direct and indirect oncostatic properties specific to colorectal cancer; for example, melatonin can cause growth inhibition of cell lines derived from colon carcinomas in vitro and animal studies 1719 . Short sleep duration (a common consequence of night shift work) and a length polymorphism in the PER3 clock gene (a genotype associated with morning chronotype and sleep disorders) have been associated with a higher risk for formation of colorectal adenoma, the precursor lesion to colorectal cancer 20, 21 . However, in a recent report, we found no evidence for an association between night shift work and risk for colorectal adenomas among female nurses 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although knowledge of Per3's role as a component of time-keeping system in humans is limited, a number of reports indicate that hPer3 can be involved in the functioning of sleep [8,24,25] and of certain metabolic processes [11,26]. Per3 alleles seem to influence sleep homeostasis and sleep/wake timing in individuals [8,9] and a strong correlation has been found between the amount of sleep time and Per3 protein secretion in individuals [27].…”
Section: Discussionmentioning
confidence: 99%
“…Per3 alleles seem to influence sleep homeostasis and sleep/wake timing in individuals [8,9] and a strong correlation has been found between the amount of sleep time and Per3 protein secretion in individuals [27]. Compared to four repeat individuals, five repeat individuals tend to experience a greater sense of sleep pressure and, further, tend to demonstrate a poorer cognitive performance when they are sleep deprived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation